Language, Identity, and Ideology: A Sociolinguistic Analysis of Discourse in Multicultural Societies - Rizki Amalia Sholihah; Ishak Bagea; Sitti Agustina (Yayasan Adra Karima Hubbi, 2026)
Background. Language plays a fundamental role in shaping and reflecting identity, particularly in multicultural societies where diverse linguistic and cultural backgrounds intersect. The relationship between language, identity, and ideology is complex, as discourse both constructs and reflects social realities, power dynamics, and cultural values. Understanding how language operates in such contexts is crucial for exploring how ideologies are communicated and contested. Purpose. This study aims to examine the interplay between language, identity, and ideology in multicultural societies through a sociolinguistic analysis of discourse. It seeks to understand how language is used to construct social identities, negotiate cultural differences, and reinforce or challenge dominant ideologies within diverse communities. Method. A qualitative sociolinguistic approach is employed, using discourse analysis to examine a range of spoken and written texts from multicultural settings. Data sources include media, political speeches, and everyday conversations. The analysis focuses on how linguistic choices reflect identity construction and ideological positioning. Results. The findings reveal that language is a powerful tool for constructing social identities, with speakers strategically using linguistic features to align themselves with particular cultural or political groups. Ideological discourses are often reinforced through language, but also provide spaces for resistance and the negotiation of power relations. Conclusion. This study demonstrates the significant role of language in shaping identity and ideology in multicultural societies, highlighting the need for continued research into how language practices contribute to social dynamics and political discourse.